2010
DOI: 10.1021/jp102451w
|View full text |Cite
|
Sign up to set email alerts
|

Alignment and Relaxation Dynamics of Dye Molecules in Host−Guest Inclusion Compounds As Probed by Dielectric Spectroscopy

Abstract: The alignment and relaxation dynamics of a polar dye molecule, N,N-dimethyl-4(4-nitrophenylazo)aniline (DNAA), in zeolite L and perhydrotriphenylene (PHTP) channels were investigated by means of a combination of optical, dielectric, and quantum-chemical methods. Both the zeolite L and PHTP channels enable the dye molecules to align along the channel axis. An amplified net dipole moment of DNAA in PHTP is observed and attributed to enhanced 1D close alignment of dye molecules. In zeolite L channels, a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…Chromophores bearing a positive charge – from the simplest ones like thionine,,,,, xanthene dyes,,,,,, acridine (and derivatives),,,,, to more complex molecules like methylviologen or BODIPY‐dyes,,, – are naturally prone to be incorporated by a zeolite via straightforward ion exchange, a practice which is also used for dye incorporation into anionic MOF nanochannels ,. As a consequence, cationic dyes are very popular as luminescent guests, and their encapsulation has been widely documented by experimental, theoretical, or combined investigations.…”
Section: Organization Of Complex Species In 1dmentioning
confidence: 99%
“…Chromophores bearing a positive charge – from the simplest ones like thionine,,,,, xanthene dyes,,,,,, acridine (and derivatives),,,,, to more complex molecules like methylviologen or BODIPY‐dyes,,, – are naturally prone to be incorporated by a zeolite via straightforward ion exchange, a practice which is also used for dye incorporation into anionic MOF nanochannels ,. As a consequence, cationic dyes are very popular as luminescent guests, and their encapsulation has been widely documented by experimental, theoretical, or combined investigations.…”
Section: Organization Of Complex Species In 1dmentioning
confidence: 99%
“…44 PHTP provides a tight environment due to the narrow channels; on the other hand, the channel walls should be rather soft, since the crystal is held together by van der Waals forces only. To monitor the guest dynamics, a number of different spectroscopic techniques were investigated, including fluorescence excitation, 21 Raman, 9 2 H-NMR, 21 and dielectric investigations, 22 accompanied by quantum-chemical 9,21,22 and molecular mechanics/dynamics (MM/MD) studies, 21 see Fig. 4.…”
Section: Modeling Of Energy Transportmentioning
confidence: 99%
“…21 Finally, the dielectric study on terminal donor-acceptor substituted stilbene guest molecules in PHTP showed that intramolecular rotational mobility is suppressed in the tight channels, but instead collective intermolecular mobility is enhanced through dipole amplification and weak hydrogen bonds. 22…”
Section: Modeling Of Energy Transportmentioning
confidence: 99%
See 2 more Smart Citations